The effects of e-trust, e-service quality and e-wom to e-loyalty with e-satisfaction as an intervening variables of jenius app users in Jakarta - Witha Dainy Sulistio; Aam Bastaman (Enrichment : Journal of Management, 2023)
he era development in corporate management is required to be able to determine strategies and innovation to survive in business competition, so that it can keep customer satisfaction. There is one of the application, namely Jenius application that must maintain customers. There are some purposes in this study, such as to determine whether E-Trust affects E-Satisfaction Jenius users, whether E-Service Quality affects the E-Satisfaction of Jenius users, whether E-WOM quality affects the E-Satisfaction of Jenius users, whether E-Trust affects E-Loyalty of Jenius users, whether E-Service Quality affects the E-Loyalty of Jenius users, whether E-WOM affects E-loyalty of Jenius users, whether E-Satisfaction affects E-Loyalty of Jenius users, whether E-Service quality affects E-Loyalty of Jenius users through E-Satisfaction as an intervening variable of Jenius users, whether E-Trust affects E-Loyalty of Jenius users through E-Satisfaction as an intervening variable, and whether E-WOM affects E-Loyalty of Jenius users through E-Satisfaction as an intervening variable. This research method employed descriptive research with quantitative approach. The results of this study revealed that the effects of E-Trust, E-Service Quality, and E-WOM on E-Loyalty mediated E-Satisfaction. This research involved 130 respondents of Jenius customers who are active and domiciled in Jakarta.